Comparison of a computerized algorithm and prosthetists' judgment in rating functional levels based on daily step activity in transtibial amputees. (September 2016) - Orendurff, Michael S; Kobayashi, Toshiki; Villarosa, Christopher Q; Coleman, Kim L; Boone, David A
The Medicare Functional Classification Levels: "K-Level" system is a standard scale for functional levels of amputees. But it is problematic to document objectively and reliably. The K-Levels are based on three characteristics: potential to ambulate, cadence variability and energy level of the amputees. Actual mobility patterns of transtibial amputees recorded by a step activity monitor (StepWatch™) were translated using a computerized algorithm to match the three K-Level characteristics: the most active one minute, the ratio of low:medium:high step rates, and the total daily steps, respectively. This study compared prosthetists' ratings of functional levels based on a visual inspection of step activity patterns with the ratings calculated by the computerized algorithm based on the same step activity data in 81 transtibial amputees. The computerized algorithm produced functional level values that closely matched the average of the ratings by 14 experienced prosthetists. The slope of the linear regression line was 1.04 with an R 2 value of 0.829, indicating good linearity and concordance across the range of the two scales. The results of this study demonstrated concurrent validity of the computerized algorithm and suggested that it could potentially serve as a useful tool in rating functional levels of transtibial amputees based on real-world step activities and complement a clinic-based test.